The Potential of Rice Husk and Softwood Biochar in Enhancing Nutrient Enrichment of Soil Following Digestate Application - M, Abdulrasheed; A, Bashir R. (Darul Yasin Al Sys, 2025)
As global consumption of agricultural products continues to rise due to population growth, the volume of agricultural waste generated also increases, necessitating sustainable waste management strategies. Digestate, a nutrient-rich byproduct of anaerobic digestion, has been widely utilized as an organic fertilizer. However, concerns persist regarding environmental pollution caused by nutrient leaching and ammonia volatilization, particularly when excessive nutrients are applied to soil. This study investigates the potential of standard biochar derived from rice husk and softwood to mitigate these environmental risks. A pot trial was conducted using 300g of loamy soil per pot, with treatments including rice husk biochar, softwood biochar (both at 1:10 w/w), and a control group with untreated soil, all prepared in duplicate. Anaerobic digestate was applied to each treatment at a ratio of 1:10 v/w. The experiment simulated heavy rainfall to assess nutrient leaching under different soil amendment conditions. Nutrient concentrations in the resulting leachates were measured using HACH Lange cuvette kits. Results revealed the short-term impact of biochar amendments on nutrient retention in loamy soils. The findings suggest that both rice husk and softwood biochar have potential to reduce nutrient loss through leaching, thus offering a promising strategy for sustainable nutrient management in agricultural systems.